Secure on-demand routing protocol in wireless sensor networks based on route weight and knowledge sharing - Farrokhtala, Ali (2013)
Due to the rapid growth of wireless sensor network's applications, the lack of appropriate secure protocol is so sensible. Meanwhile, a huge number of researches have been done to fulfill these security principles but still there is not any approved standard in this field. Black hole attack as one of the most common insider attacks of Ad hoc networks has been targeted in this research. Black hole attack is occurred when one node or a group of compromised nodes begin to make a disruption in network routing through dropping of every received packet. Many security mechanisms are presented to detect and mitigate this attack that one of them is route weight method. However, our contribution is combining this technique with the knowledge sharing concept. In order to achieve this goal some modifications are applied to algorithm and source code of Ah hoc On-demand Distance Vector routing protocol. AODV is one of the lightweight protocols in the wireless network that is not secure by itself. As a result of employed mentioned security mechanisms into AODV make it possible to protocol continue to its procedure at the present of adversarial nodes and black hole attacks as far as a safe route exists between source and destination. Conversely, simulation results show that it caused a small amount of overload packet but still has great performance even in comparison to be other proposed protocols.